Implementasi Metode Pembelajaran Tahfidzul Qur’an untuk Meningkatkan Kecakapan Menghafal Al-Qur’an Siswa - Fajeri, Ahmad Alghifari (Anterior Jurnal, 2016)
The aim of this study is to know how far the implementation of the method of Tahfidzul Qur'an in improving the students’ ability in memorizing Qur'an and any factors that can make the method can be effective or not in its implementation in Elementary School of Integrated of Tahfidzul Qur'an An-Najah Martapura. This study used a qualitative approach. The approach is by describing the data collected in the field, creating a picture or painting systematically, factually and accurately about the learning methods of Tahfidzul Qur'an in Elementary School of Integrated of Tahfidzul Qur'an An-Najah Cindai Alus Martapura. The results of this study showed that the implementation of the method of Tahfidzul Qur'an in improving the students’ ability in memorizing Qur'an in Elementary School of Integrated of Tahfidzul Qur'an An-Najah Martapura is in a good category, although, of course, it still has many matters that have to be developed. The patience of the Ustadzah/teachers is the factor that plays an important role in guiding students, especially at the basic education level. But, the matter that affects the learning implementation Tahfidzul Qur'an in Elementary School of Integrated of Tahfidzul Qur'an An-Najah Martapura become effective or not is the condition of students who tend to vary so that sometimes the learning is not so optimal.